2003
DOI: 10.1021/bi027290b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of Human Methionine Synthase Reductase:  Determination of the Flavin Redox Potentials in Full-Length Enzyme and Isolated Flavin-Binding Domains

Abstract: Human methionine synthase reductase (MSR) catalyzes the NADPH-dependent reductive methylation of methionine synthase. MSR is 78 kDa flavoprotein belonging to a family of diflavin reductases, with cytochrome P450 reductase (CPR) as the prototype. MSR and its individual flavin-binding domains were cloned as GST-tagged fusion proteins for expression and purification from Escherichia coli. The isolated flavin domains of MSR retain UV-visible and secondary structural properties indicative of correctly folded flavop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 36 publications
5
71
1
Order By: Relevance
“…These values are in agreement with the redox potentials obtained from this work for the FMN of the soluble diflavin WT rat CYPOR (Ϫ56 mV for FMNox/sq and Ϫ249 mV for FMN sq/hq) at pH 7.4. Previous experiments on diflavin reductases have shown that the potentials of the FMN domain are similar in the diflavin and separate flavin domains (29,58,59). Because of the confounding presence of both FAD and FMN in the diflavin CYPOR, the FMN redox potentials could not be unambiguously assigned for the diflavin ⌬Gly-143 and two ⌬Gly-141 mutants.…”
Section: Determination Of the Redox Potentials Of The Fmn Domainsmentioning
confidence: 94%
“…These values are in agreement with the redox potentials obtained from this work for the FMN of the soluble diflavin WT rat CYPOR (Ϫ56 mV for FMNox/sq and Ϫ249 mV for FMN sq/hq) at pH 7.4. Previous experiments on diflavin reductases have shown that the potentials of the FMN domain are similar in the diflavin and separate flavin domains (29,58,59). Because of the confounding presence of both FAD and FMN in the diflavin CYPOR, the FMN redox potentials could not be unambiguously assigned for the diflavin ⌬Gly-143 and two ⌬Gly-141 mutants.…”
Section: Determination Of the Redox Potentials Of The Fmn Domainsmentioning
confidence: 94%
“…Extensive studies of the interactions of purified hMSR with NADPH have been performed (15)(16)(17). However, overexpression of an active recombinant hMS has heretofore not been achieved, preventing biochemical studies of the interactions between hMS and hMSR.…”
mentioning
confidence: 99%
“…The eukaryotic NOS isoforms, like P450 BM3, contain heme b bound to an oxygenase domain covalently linked to the reductase domain (18). In recent work, the reduction potentials for each of the couples of the flavin cofactors in P450 BM3, neuronal NOS, human CPR, human novel reductase 1, and methionine synthase reductase have been determined by anaerobic spectroelectrochemistry (6,10,(17)(18)(19).…”
mentioning
confidence: 99%